Information technologies as one of the important factors in the development of the effectiveness of internal audit - Ramazanova, K.M.; Nurgaliyeva А.М. (BUKETOV BUSINESS REVIEW, 2023)
Object: The main idea of the research work is to define the usage of information technology concept of internal audit in the commercial organisations in Kazakhstan and its impact on the effectiveness of internal audit. There were many reasons to switch to a new way of working: pandemic during COVID 19, new IT technologies and also new market demands. Methods: The collected theoretical and practical data were analysed using the SWOT analysis and structuring information. Findings: IT transformation in the business after pandemic reveals new opportunities for internal audit, however at the same time it opens up new technological risk which lead to new threats. So the internal audit should decrease the risk to the acceptable level, the article offers several ways to mitigate these risks. Conclusions: Remote audit will not be able to replace the on-site audit; however, the transformation has started. It was caused not only due to pandemic reasons, but also due to the the development of the market and information technologies